2013
DOI: 10.1371/journal.pone.0071971
|View full text |Cite
|
Sign up to set email alerts
|

Visualized Computational Predictions of Transcriptional Effects by Intronic Endogenous Retroviruses

Abstract: When endogenous retroviruses (ERVs) or other transposable elements (TEs) insert into an intron, the consequence on gene transcription can range from negligible to a complete ablation of normal transcripts. With the advance of sequencing technology, more and more insertionally polymorphic or private TE insertions are being identified in humans and mice, of which some could have a significant impact on host gene expression. Nevertheless, an efficient and low cost approach to prioritize their potential effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Genomic copies of HERVs are of particular interest because in addition to functional viral genes, they have multitude of regulatory DNA regions serving as promoters [1][2][3], enhancers [4,5], polyadenylation signals [6,7], insulators [8,9] and binding sites for various nuclear proteins [2,[10][11][12][13]. Many families of HERVs exhibit high transcriptional activity in human tissues [1,[14][15][16][17]. HERVs are believed to be remnants of numerous retroviral infections [18][19][20] that occurred repeatedly during primate evolution [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic copies of HERVs are of particular interest because in addition to functional viral genes, they have multitude of regulatory DNA regions serving as promoters [1][2][3], enhancers [4,5], polyadenylation signals [6,7], insulators [8,9] and binding sites for various nuclear proteins [2,[10][11][12][13]. Many families of HERVs exhibit high transcriptional activity in human tissues [1,[14][15][16][17]. HERVs are believed to be remnants of numerous retroviral infections [18][19][20] that occurred repeatedly during primate evolution [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…RASGRF2-int, like the majority of HK2 intronic integrations of the human genome, is antisense compared with RASGRF2 (10). Intronic ERVs in mice are mostly antisense and the majority of them do not disrupt normal gene transcription (26), while a minority of antisense intronic mouse ERVs have been shown to disrupt transcription (26,28). The alternative explanation for the above-found associations is that RASGRF2-int is a proxy of a genetically linked (yet unknown to us) polymorphism of RASGRF2, which bears the true causal effect.…”
Section: Artificial Insertion Of the Hk2 Ltr Can Modulate Rasgrf2mentioning
confidence: 99%
“…Our primary hypothesis is that RASGRF2-int is modulating transcription of RASGRF2 ( Fig. 1), as some intronic ERVs have been shown to modulate transcription in mice (12,26,27). RASGRF2-int, like the majority of HK2 intronic integrations of the human genome, is antisense compared with RASGRF2 (10).…”
Section: Artificial Insertion Of the Hk2 Ltr Can Modulate Rasgrf2mentioning
confidence: 99%
“…ML and DL fields are supported by multiple companies and industry research groups, which anticipated the great benefits that artificial intelligence can contribute to genomics, human health (Eraslan et al, 2019), and major crops. Several papers using ML or DL techniques reported that TEs are associated with many human diseases (Zhang et al, 2013). For example, cancer-related long noncoding RNAs have higher SINE and LINE numbers than cancer-unrelated long noncoding RNAs (Zhang et al, 2018).…”
Section: Benefits Of ML Over Bioinformatics (Q1)mentioning
confidence: 99%
“…PRISMA flow diagram Publication identifier Year Q1 Q2 Q3 Q4 Reference Publication identifier Year Q1 Q2 Q3 Q4 Reference P1 X X X X (Yu, Yu & Pan, 2017) P19 2013 X X X (Loureiro et al, 2013b) P2 X X X (Schietgat et al, 2018) P20 2014 X X (Ma, Zhang & Wang, 2014) P3 X X X (Arango-López et al, 2017) P21 2010 X X (Dashti & Masoudi-Nejad, 2010) P4 X X X (Loureiro et al, 2013a) P22 2010 X X (Ding, Zhou & Guan, 2010) P5 X X X (Tsafnat et al, 2011) P23 2019 X (Jaiswal & Krishnamachari, 2019) P6 X X X (Zhang et al, 2018) P24 2015 X X X X (Girgis, 2015) P7 X X X (Eraslan et al, 2019) P25 2018 X X X (Nakano et al, 2018a) P8 X X X (Douville et al, 2018) P26 2018 X X X (Zamith Santos et al, 2018) P9 X X (Chen et al, 2018) P27 2009 X (Abrusan et al, 2009) P10 X X X X (Ashlock & Datta, 2012) P28 2019 X X (Su, Gu & Peterson, 2019) P11 X X X (Smith et al, 2017) P29 2017 X X X X (Nakano et al, 2017) P12 X X X X (Kamath, De Jong & Shehu, 2014) P30 2014 X X X (Brayet et al, 2014) P13 X X X (Kim et al, 2016) P31 2013 X (Zamani et al, 2013) P14 X X X (Segal et al, 2018) P32 2019 X (Hubbard et al, 2019) P15 X X X (Rawal & Ramaswamy, 2011) P33 2014 X X (Ryvkin et al, 2014) P16 X X X (Tang et al, 2017) P34 2013 X X X X (Zhang et al, 2013) P17 X X X (Ventola et al, 2017) P35 2019 X X…”
Section: Figurementioning
confidence: 99%